Evaluación de la calidad del servicio de abastecimiento de agua potable a partir de la percepción de personas usuarias: El caso en Cartago, Costa Rica - Cruz Zúñiga, Nidia (2020)
Costa Rica needs to improve the drinking-water supply service of an important part of the po- pulation, aiming to ensure the access to this vital resource considered as a human right. [Objective]: This study evaluated the perception of the population of four cities of the province of Cartago (Alvarado, Jiménez, Oreamuno, and Turrialba) about the public drinking-water supply service they receive in their communities. [Methodology]: The analysis considered both the geographic location of the population and the type of service provider to show the similarities and contrasts found in each case. Through surveys, the opinion of 2,194 users of the drinking water systems of these localities was collected. [Results]: It was found that there are considerable asymmetries between many of the existing systems, with some problems at the level of service continuity and organoleptic propertiesof the liquid. The study identified a strong dependence between the variables of i) level of user satisfaction, ii) problems identified in the system, and iii) actions implemented by users to mitigate these shortcomings. [Conclu- sions]: The experience resulting from this study of evaluating the water supply service in a community through the perception of its users complements the traditional service indicators. The experience also has a high potential to be replicated in other communities of Costa Rica and other countries of Latin America and the Caribbean.